Health beliefs, lifestyle, and cognitive aging among Chinese community residents: A structural equation model analysis - Zhang, Jinying; Liu, Xiao; Gong, De; Peng, Yan; Li, Hua; Yang, Yanni (Frontiers in Public Health, 2022)
Background: Lifestyle factors may could help maintain cognitive function and reduce the risk of dementia. The application of the Health Belief Model (HBM) has been verified by incorporating lifestyle changes for dementia risk reduction; however, the influence of health beliefs on cognitive aging through lifestyle remains unknown. To facilitate research-based interventions to promote successful cognitive aging, we explored the relationship between health beliefs, lifestyle, and cognitive aging based on the HBM using path analysis. Methods: This cross-sectional study recruited middle-aged and older community residents from a community health service center in Chongqing, China, through convenience sampling. Motivation To Change Lifestyle And Health Behaviors For Dementia Risk Reduction (MCLHB-DRR), Lifestyle For Dementia Risk Reduction (LDRR), and the Montreal Cognitive Assessment (MoCA) were employed to measure participants' beliefs, lifestyle, and cognitive function, respectively. The associations between the beliefs, lifestyle, and cognitive function were analyzed, and a structural equation model was constructed. Results: A total of 202 participants completed the questionnaires, of whom only 17 (8.4%) were classified as having successful cognitive aging. The model demonstrated the data to have an acceptable fit and elucidated 40.6 and 17.5% of the variance in lifestyle and the grade of cognitive aging, respectively. Positive and negative beliefs had opposite effects on the grade of cognitive aging through lifestyle. Cues to action had opposite effects on the grades of cognitive aging through positive and negative beliefs; however, the total effects cancelled each other out. Conclusions： Positive beliefs have a positive effect on lifestyle, thereby promoting successful cognitive aging, whereas negative beliefs have a negative effect on lifestyle, thereby hindering successful cognitive aging. Health education and media publicity, as specific aspects of cues to action, can have a meaningful impact on healthy behavior and successful cognitive aging by promoting positive beliefs and controlling negative beliefs. The model suggests the strengthening and weakening of the positive and negative beliefs, respectively, of middle-aged and older community residents in the formulation of relevant public health strategies in the future, thereby enabling them to adapt to a healthy lifestyle promoting successful cognitive aging.